Carrier-directed targeting of liposomes and erythrocytes to denuded areas of vessel wall. - Smirnov, V N (1986)
Immunomorphological staining of specimens prepared from human carotid arteries with anti-collagen type I antibodies reveals large amounts of type I collagen in the subendothelium of lipid fibrous plaques. Collagen type I-containing structures, once in direct contact with blood after plaque rupture, can serve as potential targets for selective delivery of liposomes and erythrocytes to these areas. To verify this rationale, [14C]cholesterol oleate-containing liposomes were conjugated with bovine or human anti-collagen type I antibodies or human plasma fibronectin. Biotin derivatives of human anti-collagen type I antibody were coupled to human erythrocytes. Modified liposomes and erythrocytes were perfused in situ through segments of bovine, rabbit, or human arteries partially denuded with a balloon catheter prior to perfusion. After perfusion, the control and denuded areas were excised and subjected to scanning electron microscopic analysis and measurements of associated radioactivity. It was found that conjugates of liposomes or erythrocytes with anti-collagen type I antibodies or fibronectin are selectively bound by endothelium-free zones of arterial segments. Carrier-directed targeting of drug-laden liposomes and erythrocytes to thrombosis-prone areas of arterial lumen is discussed.